GE_GERICHTE P/18262/2011 vom 8. Juni 2012 - GE Cour de justice (2012)
; FIXATION DE LA PEINE ; CONCOURS D'INFRACTIONS ; SURSIS À L'EXÉCUTION DE LA PEINE ; RÉVOCATION(EN GÉNÉRAL) | CP.47; CP.46.1; CP.46.2; CP.49